Growth Response of Vanilla Stem Cuttings (Vanilla planifolia andrews) To Soaking Duration dnd Roots-90 Concentration: Respon Pertumbuhan Stek Batang Vanili (Vanilla planifolia andrews) Terhadap Lama Perendaman dan Konsentrasi Roots-90 - Tangguh Prakoso; Heny Alpandari; Nabila Putri Maghfiroh (Universitas Muhammadiyah Sidoarjo, 2026)
Vanilla plants (Vanilla planifolia Andrews) are generally reproduced vegetatively using stem cuttings. However, this vegetative propagation method still faces several obstacles, such as the limited availability of stem cuttings as a source of seeds and the growth of roots and shoots which takes a long time, making stem cuttings susceptible to stem rot. One way to increase the growth of cuttings is to stimulate root growth. One of the nutrients that stimulates plant root growth is Roots-90, which has similar functions and characteristics to other PGRs. Research was conducted at the Experimental Garden of the Faculty of Agriculture, Muria Kudus University, which aimed to evaluate the response to the concentration and soaking time of Roots-90. affects the initial growth of vanilla stem cuttings (Vanilla planifolia Andrews). This research was conducted from March to June 2023. The method used was a factorial experiment with a Complete Randomized Group Design (RAKL), which involved 2 factors and 3 replications. The first factor of Roots-90 concentration consists of 3 levels, namely 0 ml/l, 2 ml/l, and 4 ml/l. The second factor for soaking time in Roots-90 consists of 3 levels, namely 0 minutes, 120 minutes and 180 minutes. The research results showed that the higher concentration and soaking time of Roots-90 had a positive impact on the success of propagating vanilla stem cuttings, especially on shoot growth.